Legitimate Expectations of Privacy in the Era of Digitalization - E. Ostanina; E. Titova (BRICS Law Journal)
This article contends that in the present era of digitalization people’s right to privacy should be protected no less than it was before the widespread use of digital technologies. When taking into account the fact that digitalization has led to a greater exchange of information, it is important that the ways and forms of protecting privacy undergo certain changes. Firstly, more emphasis should be placed on the use of methods for the self-protection of privacy rights, including restricting access to information and configuring website settings so that reviews and comments can be posted only by registered users, and not anonymously. Secondly, the legal means of protection should be improved to prevent violations of privacy rights from occurring as well as to ensure that rights which have been violated are properly restored. In the event of a violation of the secrecy of personal data, the authors recommend the use of class actions. When a violation of the secrecy of correspondence, medical information or telephone conversations by a business entity or the owner of a website occurs, a claim for compensation for moral damage should be available. However, the authors of the article propose modifying such a claim for compensation for moral damage to more closely model a claim for the recovery of punitive damages. Furthermore, the authors establish a connection between the protection of the right to privacy and the variety of relevant information on the topic that is freely available.